Respuesta :

1. Expand
6x + a = 5x + 5t
2. Get x on one side
6x - 5x = 5t - a
3. Simplify
x = 5t - a (I think)

Answer:

x= 5t - a

Step-by-step explanation:

6x + a = 5(x+t)

If you expand 5(x+t), you will get 5x + 5t

i.e. 6x + a = 5x + 5t

Add the additive inverse of 5x to both sides (The additive inverse of 5x is -5x)

i.e. 6x + a - 5x = 5x + 5t - 5x

     x + a = 5t

Then, add the additive inverse of "a" to both sides (The additive inverse of a is -a)

i.e. x + a - a = 5t - a

x = 5t - a

Hope this helps!!!